1999
DOI: 10.1007/s11746-999-0075-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of enzymatic synthesis of isopropylidene glycerol esters by goat pregastric lipase

Abstract: The goat pregastric lipase-catalyzed esterification of isopropylidene glycerol with caproic acid, to form isopropylidene glycerol caproate, followed a ping pong bi bi mechanism incorporating an acyl-enzyme intermediate. The maximum rate was estimated to be 96 µmol min -1 mg -1 in isooctane at 35°C, and the Michaelis-Menten constants for isopropylidene glycerol and caproic acid were 0.23 and 0.32 M, respectively. The catalyzed rate also correlated well with the partition coefficient of caproic acid between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In this type of reaction, involving two substrates and two products (Bi Bi reaction), the enzyme reacts with the first substrate to give a covalently modified enzyme intermediate and then releases the second product (Ping Pong mechanism). Several other studies confirmed that experimental data for hydrolysis, esterification, alcoholysis, and ester exchange reactions catalyzed by lipases in various organic solvents were well fitted by this model [48][49][50][51][52][53][54]. In most cases, competitive inhibition by the alcohol was reported.…”
Section: Kinetics Of Reactionssupporting
confidence: 58%
“…In this type of reaction, involving two substrates and two products (Bi Bi reaction), the enzyme reacts with the first substrate to give a covalently modified enzyme intermediate and then releases the second product (Ping Pong mechanism). Several other studies confirmed that experimental data for hydrolysis, esterification, alcoholysis, and ester exchange reactions catalyzed by lipases in various organic solvents were well fitted by this model [48][49][50][51][52][53][54]. In most cases, competitive inhibition by the alcohol was reported.…”
Section: Kinetics Of Reactionssupporting
confidence: 58%
“…However, the enzymatic catalysis of the two substrates could be controlling concentration of one of the substrates. This results in the formation of a plot following Michelis-Menten relationship between the initial rate and the other substrate concentration (Lai et al, 1999). Michaelis and Menten provided an explanation regarding a mechanism of "the initial rate of enzyme-catalyzed reactions" that is highly affected by the concentration.…”
Section: Study Of Enzyme Kineticsmentioning
confidence: 99%
“…Given the nature of enzyme-catalyzed reactions, the case of a single product reaction is very rare. Most cases of enzyme-catalyzed reactions involve more than one substrate and produce two or more products (Lai et al 1999). The alcoholysis of palm oil with oleyl alcohol can be considered in this research as an enzymatic reaction system, which involves two reactants and two products.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the type of substrates, the most appropriate explanation for the lipase catalysis mechanism is ping-pong mechanism and ordered bi-bi mechanism, which involve acyl-enzyme intermediate. Lai et al (1999), combine these mechanisms to be pingpong bi-bi (i.e., bi-substrate, bi-product, non-sequential kinetics) mechanism, in which the first reactant would be involved in the reaction mechanism producing the max max (acyl migration processes) are the lowest rate constants of the whole catalytic process. In other words, acyl migration is the rate-determining step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation